The Impact of Loss and Alienation in English Language Learners - Antunes, Miguel Abrantes (Radical Teacher, 2021)
Educational institutions have the capacity to support immigrant students and English Language Learners through their emotional struggles with racial melancholia, dissociation, and cultural assimilation by utilizing validating curricula that promotes critical consciousness. Unfortunately, many secondary educational institutions routinely neglect the persistent emotional impact of racial melancholia and dissociation while instituting oppressive Eurocentric curriculum teeming with white privilege that undermines cultural diversity. A primary reason why so much modern humanities curricula is devoid of diversity and humanity is because it is subordinate to standardized testing leading to rote, ineffectual academic experiences negating the development of critical thinking skills and critical consciousness for immigrant students and English Language Learners.